Differential susceptibility in longitudinal models of gene–environment interaction for adolescent depression. (8th November 2013) - Li, James J.; Berk, Michele S.; Lee, Steve S.
Abstract: Although family support reliably predicts the development of adolescent depression and suicidal behaviors, relatively little is known about the interplay of family support with potential genetic factors. We tested the association of the 44 base pair polymorphism in the serotonin transporter linked promoter region gene ( 5-HTTLPR ), family support (i.e., cohesion, communication, and warmth), and their interaction with self-reported depression symptoms and risk for suicide in 1, 030 Caucasian adolescents and young adults from the National Longitudinal Study of Adolescent Health. High-quality family support predicted fewer symptoms of depression and reduced risk for suicidality. There was also a significant interaction between 5-HTTLPR and family support for boys and a marginally significant interaction for girls. Among boys with poor family support, youth with at least one short allele had more symptoms of depression and a higher risk for suicide attempts relative to boys homozygous for the long allele. However, in the presence of high family support, boys with the short allele had the fewest depression symptoms (but not suicide attempts). Results suggest that the short allele may increase reactivity to both negative and positive family influences in the development of depression. We discuss the potential role of interactive exchanges between family support and offspring genotype in the development of adolescent depression and suicidal behaviors.